1994
DOI: 10.1055/s-2007-1016504
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of High-Dose Ascorbic Acid on Myocardium against Reperfusion Injury During and After Cardiopulmonary Bypass

Abstract: The protective effects of high-dose ascorbic acid (250 mg/kg) on the myocardium were observed in 85 patients undergoing Cardiopulmonary Bypass (CPB). The changes in serum Malonyldialdehyde (MDA). Creatine Phosphokinase (CPK), Creatine Phosphokinase isozyme (CPK-MB) and Lactic Dehydrogenase (LDH) in group B (n = 45, receiving ascorbic acid) were lower (p < 0.05) than in group A (n = 40, no ascorbic acid) during and after CPB. The MDA remained at a higher level two days postoperatively; CPK and CPK-MB, the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 0 publications
2
76
2
2
Order By: Relevance
“…These results suggest that vitamin C suppresses the generation of free oxygen radicals, which then decreases the MDA level. Previously, Dingchao et al 15 reported that MDA levels decreased following the administration of high-dose vitamin C in patients undergoing open heart surgery. In addition, CPK-MB and lactate dehydrogenase (LDH) levels were lower in these patients, which may offer some protection for cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that vitamin C suppresses the generation of free oxygen radicals, which then decreases the MDA level. Previously, Dingchao et al 15 reported that MDA levels decreased following the administration of high-dose vitamin C in patients undergoing open heart surgery. In addition, CPK-MB and lactate dehydrogenase (LDH) levels were lower in these patients, which may offer some protection for cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As these resources are exhausted, ROS are then able to react with biological moieties in an unregulated fashion, thus producing the detrimental effects listed above. Although there are considerable controversies regarding the efficacy of exogenous antioxidants during ischemia/reperfusion injury [65], positive results have been obtained in a variety of experimental and clinical settings [67][68][69][70]. Amongst the agents tested for efficacy during ischemia/reperfusion injury are various phenols.…”
Section: Acetaminophen and Reactive Oxygen Speciesmentioning
confidence: 99%
“…Ebenso war der Herzindex in der Vitamin-C-Gruppe signifikant höher als in der Kontrollgruppe. Die Verweildauer auf der Intensivstation sowie der Krankenhausaufenthalt waren in der Behandlungsgruppe signifikant kürzer [13]. Die Ergebnisse dieser Arbeit deuten darauf hin, dass Vitamin C den ischämischen Reperfusionsschaden des Herzens während und nach offener Herzoperation vermindern kann.…”
Section: Antioxidantienunclassified